THE CONSUMERIST LIFESTYLE OF THE ZOOMER GENERATION IN RELATION TO IPHONE OWNERSHIP IN PURWOKERTO - Sharlen Taurisya Agati DJ; Hariyadi Hariyadi; Sulyana Dadan (UNIVERSITAS SEBELAS MARET (UNS), 2025)
The rapid development of digital technology has shaped the lifestyle of Generation Z, or “zoomers,” who are known as digital natives. iPhone ownership among zoomers in Purwokerto reflects not only functional needs but also symbolic consumption linked to identity and social status. This study aims to analyze how zoomers in Purwokerto interpret iPhone ownership as part of their self-identity construction. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews, observation, and documentation, which were then analyzed using the Miles and Huberman model to identify patterns of meaning. The results indicate that iPhone ownership among zoomers is closely linked to status symbols, personal branding, social integration, and the representation of a consumerist lifestyle. Although aware of the consumptive nature of this practice, the Zoomers generation continues to prioritize avoiding social pressures such as the fear of missing out (FOMO) by making the iPhone a symbol of modernity and prestige. This study concludes that the iPhone functions not only as a communication tool but also as a cultural symbol that reinforces a consumptive lifestyle while legitimizing social existence in the digital age.